ANALISIS PENAMBAHAN FASILITAS MESIN CUCI PADA USAHA LAUNDRY DEWI DI SAMARINDA - Kereh, Selviana (EKONOMIA, 2013)
Selviana Kereh, 2012, Analysis Facility Addition Washing Machines In Laundry Goddess Business Park in Dublin under the guidance of Mrs. and Mrs. Rina Titin Ruliana Masitoh Hariyadi,One of the business services ogled by the venture investor laundry or washing clothes. Laundry effort is generally undertaken by the five-star hotel, but with the increase of population, the need for laundry services is growing. In its development, business owners Laundry Goddess wishes to expand its facilities in order to improve the washing machine profits, because at certain times the capacity of existing 3 washing machines are not able to serve the demand.this study to determine the feasibility of the plan determine the addition of a washing machine brand Elektrolux 2 (two) business unit at Laundry Goddess seen from the Payback Period, Net Present Value and Internal Rate of Return. Basic theory used operational management especially regarding investments.The analysis tools analysis Payback Period, Net Present Value and IRR with a payback period of 5 years and the opportunity cost of capital of 5%. Based on the analysis and discussion, conclusion of this study: Period of return on investment of Rp. Rp. 13.1 million over 5 years 24 days. This time is longer than the life of the project for 5 years. These results indicate that the payback period longer than the life of the project, thus based on the analysis of the payback period or return on investment, the investment period is not feasible, so the first hypothesis is rejected.Net Present Value at 5% discount factor obtained presen total net value of Â Rp. 32,494,124 while total investment of Rp. 32,494,124 - Rp. 13.1 million = Rp. 19,394,000. This difference is positive and greater than one, and based on analysis of Net Present Value, the investment is feasible, according to the second hypothesis is accepted.The recovery rate of internal (Internal Rate of Return) using two interest rate is 5% and 6% and two scores Net Present Value using a discount factor of 5% and 6% Net Present Value obtained values first with 5% discount factor Rp. 32,494,124 Net Present Value and values both with 6% discount factor Rp. 31,410,073 to obtain the value of IRR of 14.34%. Because the value of 14.34% IRR greater than the opportunity cost of capital (Opportunity Cost Of Capital) of 5%, the investment is feasible, thus the third hypothesis is accepted.